Early surgery in Crohn's disease patients with entero-urinary fistulas: does it change the prognosis?. (2nd June 2016) - Coelho, Rosa; Magro, Fernando; Silva, Marco; Macedo, Guilherme
Abstract: Background Entero-urinary fistulas (EUF) are observed in only 2–8% of Crohn's disease (CD) patients.Aim To compare the outcome of patients with EUF, after surgical treatment, with those with non-penetrating and non-stenosing, penetrating, and stenosing phenotypes (B1, B2, and B3 phenotypes).Methods Case-control study of 21 CD patients with EUF submitted to surgical treatment. Each patient with EUF was compared with six patients, two of each group: B1, B2, and B3 phenotypes. They were randomly selected from inflammatory bowel disease database and had the same extent of disease, smoking status, perianal disease, and age at diagnosis.Results One hundred and forty-seven patients were included ( n  = 21 EUF; n  = 42 of each group B1, B2, and B3). Comparing B3 group with EUF, the former was more steroid-dependent and resistant (54.8% versus 19.0%, p  = 0.037) and needed anti-TNF therapy more frequently (59.5% versus 23.8%, p  = 0.004). Moreover, B3 patients had a poorer response to anti-TNF therapy without remission free of steroid therapy in comparison with EUF patients (45.2% versus 95.2%, p  < 0.001). EUF patients did not differ from B2 group regarding anti-TNF therapy ( p  = 0.956) and steroid-dependence or resistance ( p  = 0.141). Surgery rate after index surgery was inferior in EUF in comparison with B2 and B3 groups. Hospital admission rate of patients with EUF was also lower than the B3 group.Conclusion Early surgery seems to be a good choice for patients with EUF as their response to surgery appears not to differ from B2 patients and had a better prognosis than phenotype B3 patients.